2019
DOI: 10.1097/sla.0000000000003523
|View full text |Cite
|
Sign up to set email alerts
|

Management of Five Hundred Patients With Gut Failure at a Single Center

Abstract: Objective(s): To define the evolving role of integrative surgical management including transplantation for patients gut failure (GF). Methods: A total of 500 patients with total parenteral nutrition-dependent catastrophic and chronic GF were referred for surgical intervention particularly transplantation and comprised the study population. With a mean age of 45 ± 17 years, 477 (95%) were adults and 23 (5%) were children. Management strategy was guided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 61 publications
0
55
0
5
Order By: Relevance
“…However, the newly introduced “Trifecta” procedure is described to manage patients with global dysmotility with preserved liver functions, with the intent to treat or as a bridge for intestinal transplant. It consists of subtotal colectomy, chimney ileostomy and pyloroplasty [6 ▪ ]. The Trifecta procedure is not effective for patients with global GD with massive gut dilatation [40 ▪ ].…”
Section: Surgical Rehabilitaion For Dysmotility Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…However, the newly introduced “Trifecta” procedure is described to manage patients with global dysmotility with preserved liver functions, with the intent to treat or as a bridge for intestinal transplant. It consists of subtotal colectomy, chimney ileostomy and pyloroplasty [6 ▪ ]. The Trifecta procedure is not effective for patients with global GD with massive gut dilatation [40 ▪ ].…”
Section: Surgical Rehabilitaion For Dysmotility Diseasementioning
confidence: 99%
“…The procedure helps to alleviate abdominal pain, restore oral tolerance and ameliorate the bacterial overgrowth symptoms. A recent study showed that the Trifecta is superior to the single or combined reductive/decompressive procedures in restoring full nutritional autonomy with a 3-year success rates of 71% and 55%, respectively [6 ▪ ]. The Trifecta procedure achieved a better quality of life compared to transplantation with higher performance and fewer hospital re-admissions.…”
Section: Surgical Rehabilitaion For Dysmotility Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Maßnahmen, die eine zunehmende orale Autonomie der Patienten ermöglichen, werden hauptsächlich nach Erreichen der Stabilisierungsphase der Patienten begonnen. Chirurgisch sind vor allem rekonstruktive Eingriffe (autologe Darmrekonstruktion AGR) der Darmkontinuität und der Bauchdecke zu nennen [20]. Des Weiteren sind medikamentöse sowie ernährungsmedizinische Maßnah-men und in Einzelfällen spezifische KDS-Behandlung bspw.…”
Section: Kostenberechnung Der Ambulanten Labormedizinischen Leistungunclassified